Workflow to improve patient recruitment for clinical trials within hospital information systems – a case-study - Müller-Tidow Carsten; Berdel Wolfgang E; Lange Matthias; Dugas Martin (Trials, 2008)
Abstract Background The identification of suitable patients is a common problem in clinical trials that is especially evident in tertiary care hospitals. Methods We developed and analysed a workflow, which uses routine data captured during patient care in a hospital information system (HIS), to identify potential trial subjects. Study nurses or physicians are notified automatically by email and verify eligibility. Results As a case study we implemented the system for acute myeloid leukemia (AML) trials in Münster. During a test period of 50 days 41 patients were identified by the system. 13 could be included as new trial patients, 7 were already included during earlier visits. According to review of paper records no AML trial patient was missed by the system. In addition, the hospital information system further allowed to preselect patients for specific trials based on their disease status and individual characteristics. Conclusion Routine HIS data can be used to support patient recruitment for clinical trials by means of an automated notification workflow.